Powdered cosmetics
By increasing the content of glass chips and adding fine-grained titanium oxide and liquid oil, the problem of powder solid cosmetics maintaining impact resistance and mold forming while improving transparency and gloss, achieving high transparency and high gloss feeling of cosmetic films.
Patent Information
- Application Number
- JP2020215464
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-12-27
- Filing Date
- 2020-12-24
- Publication Date
- 2025-04-16
- Estimated Expiration
- 2040-12-24
AI Technical Summary
While improving transparency and gloss, existing powder solid cosmetics are difficult to maintain good impact resistance and mold forming properties.
Powder solid cosmetics are made by increasing the content of glass chips to 20-30% and adding an appropriate amount of fine-grained titanium oxide and liquid oil.
It achieves the clear and transparent cosmetic film and high gloss feeling, while maintaining good impact resistance and comfort.
Smart Images

Figure 0007663354000001 
Figure 0007663354000002 
Figure 0007663354000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a solid cosmetic preparation in powder form. More specifically, the present invention relates to a solid cosmetic preparation in powder form that contains a large amount of glass flakes to improve transparency and gloss while also exhibiting excellent impact resistance. [Background technology]
[0002] In powdered solid cosmetics such as eye shadow, pearlescent agents (lustrous pigments) have been blended to provide variation in color and texture. However, pearlescent agents are generally known to reduce the moldability and impact resistance of cosmetics. To address this issue, extender pigments such as talc have been blended to improve moldability, but the inclusion of extender pigments can result in a loss of transparency and pearly feel in the coating film.
[0003] Patent Document 1 describes that an eye shadow with excellent pearly feel and impact resistance can be obtained by combining a large amount of pearling agent (60% by weight or more) with a liquid oil and a solid oil having an inorganic value / organic value (i.e., IOB value) of 0.1 or more. Patent Document 2 describes that a powdered solid cosmetic containing a predetermined amount of (a) boron nitride, (b) a luster pigment, and (c) an oil agent has excellent pearly feel without compromising press moldability, impact resistance, transparency during application, or usability.
[0004] Other known luster pigments (pearl agents) include glass flakes and silica flakes in addition to the mica titanium used in Patent Documents 1 and 2. For example, Patent Document 3 discloses a powdered solid cosmetic (eye shadow) that combines glass flakes with an average particle size of 65 to 180 μm with boron nitride with an average particle size of 9 to 25 μm, petrolatum, ester oil, and metal soap, and claims that by adjusting the blending ratio of boron nitride and metal soap within a specified range, a cosmetic with high transparency and excellent impact resistance can be obtained.
[0005] Patent Document 4 suggests that transparency, luster, and impact resistance can be further improved by using boron nitride with a larger average particle size than that described in Patent Document 3 and blending synthetic phlogopite with an average particle size of preferably 10 μm or more and an aspect ratio of 50 or more. Patent Document 4 does not specify the average particle size of the glass flakes, but with reference to Patent Document 3, desired properties including impact resistance cannot be obtained unless the average particle size of the blended glass flakes is less than 65 μm (Comparative Example 5). In addition, since the glass flakes are glittering pigments whose surfaces are coated with titanium oxide or the like, the pearlescent effect may be too strong. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Japanese Patent Application Publication No. 7-215822 [Patent Document 2] JP 2000-186012 A [Patent Document 3] JP 2010-77043 A [Patent Document 4] JP 2018-8906 A DISCLOSURE OF THEINVENTION [Problem to be solved by the invention]
[0007] In view of the above-mentioned current state of the art, the present invention has an object to provide a solid cosmetic preparation in powder form that exhibits transparency and excellent glossiness by incorporating a large amount of glass flakes and also has good impact resistance. [Means for solving the problem]
[0008] As a result of intensive research into achieving the above-mentioned object, the inventors have discovered that by increasing the amount of glass flakes to 20 to 30 mass % and incorporating a specified amount of fine particle titanium dioxide and a specified amount of liquid oil, a powder solid cosmetic preparation that imparts transparency and luster while also having excellent impact resistance can be obtained, thereby completing the present invention.
[0009] That is, the present invention provides (a) 20-30% by mass glass flakes; (b) 4 to 10 mass % fine particle titanium dioxide; and (c) A solid cosmetic preparation in powder form is provided, which contains 11 to 15% by mass of liquid oil. Effect of the Invention
[0010] The solid cosmetic preparation in powder form of the present invention contains 20-30% by mass of glass flakes, whereas conventionally the content was only about 10% by mass at most, and therefore the cosmetic film is excellent in transparency and luster. Furthermore, the incorporation of a predetermined amount of fine titanium dioxide particles and a predetermined amount of liquid oil provides good moldability, and the molded solid cosmetic preparation in powder form has excellent usability and impact resistance, even though it contains a large amount of glass flakes. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The solid cosmetic preparation in powder form of the present invention (hereinafter, simply referred to as "cosmetic preparation") contains (a) glass flakes, (b) fine particle titanium dioxide, and (c) liquid oil as essential components. The details are described below.
[0012] (a) Glass flakes The glass flakes (also referred to as component (a)) blended in the cosmetic of the present invention are not particularly limited as long as they are typically used in cosmetics, etc., but are preferably plate-like (scale-like) in shape. Therefore, the glass flakes in the present invention are sometimes called "plate glass powder" or "scale-like glass."
[0013] (a) The thickness of the glass flakes is preferably 0.1 to 1 μm on average, more preferably 0.2 to 0.8 μm. The average particle size of the glass flakes (D50: particle size corresponding to 50% cumulative mass percentage) is preferably 1 to 50 μm, more preferably 5 to 30 μm, and even more preferably 10 to 25 μm. The aspect ratio (value obtained by dividing the average particle size by the average thickness) is preferably 10 or more. In addition, it is preferable to use glass flakes with a uniform particle size in terms of appearance and usability, and for example, it is preferable to use glass flakes with a particle size distribution index (D90 / D10) of 5.0 or less, which is obtained by dividing the particle size (D90) corresponding to 90% cumulative mass from the smaller particle size side by the particle size (D10) corresponding to 10% cumulative mass from the smaller particle size side in the particle size distribution.
[0014] The (a) glass flakes in the present invention are preferably surface-untreated scaly calcium aluminosilicate glass (borosilicate glass) powder, but may be coated with one or more precious metals, metal oxides, and / or silica in some cases. Examples of such glass flakes include titanium oxide-coated glass flakes, silver-coated glass flakes, gold-coated glass flakes, and iron oxide-coated glass flakes.
[0015] The (a) glass flakes used in the present invention may be commercially available products, such as Silky Flake (registered trademark) FTD010FY-F01 (average particle size 10 μm) and Silky Flake (registered trademark) FTD025FY-F02 (average particle size 25 μm) manufactured by Nippon Sheet Glass Co., Ltd.
[0016] The blending amount of (a) glass flakes in the cosmetic of the present invention is 20 to 30 mass %, preferably 20 to 25 mass %, based on the total amount of the cosmetic (the same applies below unless otherwise specified). If the blending amount of glass flakes is less than 20 mass %, the transparency of the cosmetic film becomes insufficient, and if it is blended in excess of 30 mass %, the impact resistance decreases.
[0017] (b) Titanium dioxide particles The fine particle titanium dioxide (also referred to as component (b)) blended in the cosmetic of the present invention is fine particle titanium dioxide having an average primary particle diameter of 10 nm to 100 nm, more preferably 10 nm to 50 nm. The average particle diameter is measured by a method such as the number average diameter by image analysis of a transmission electron microscope photograph.
[0018] In addition, it is preferable that the (b) fine titanium oxide particles in the present invention are those whose surfaces have been hydrophobized. The method of hydrophobization is not particularly limited, and can be a known method. For example, treatment using silicones such as methylhydrogenpolysiloxane, methylhydrogenpolysiloxane-dimethylpolysiloxane copolymer, dimethylpolysiloxane, etc.; treatment using silane compounds such as octyltriethoxysilane, hexyltrimethoxysilane, etc.; treatment using fatty acids such as palmitic acid, stearic acid, etc.; metal soap treatment using metal salts of the fatty acids, etc.; fluorine treatment using perfluoroalkylphosphoric acid diethanolamine salt, perfluoroalkyltrimethoxysilane, etc., etc. can be mentioned.
[0019] The blending amount of (b) fine particle titanium dioxide in the present invention is 4 to 10% by mass, preferably 5 to 8% by mass. If the blending amount is less than 4% by mass, the powder cosmetic is not densely molded, and tends to have too much "stickiness," and the impact resistance is also insufficient. If the blending amount exceeds 10% by mass, the creaking sound peculiar to fine particle titanium dioxide is felt when applied, which is undesirable.
[0020] As described later in the description of the manufacturing method, the (b) fine particle titanium dioxide used in the present invention is added separately to and mixed with the (a) glass flakes, and is not previously attached to the surface of the glass flakes and blended in. Therefore, in the cosmetic of the present invention, the (a) glass flakes, (b) fine particle titanium dioxide, and other blended ingredients are considered to be dispersed approximately uniformly.
[0021] (c) Liquid oil The liquid oil (also referred to as component (c)) blended in the cosmetic of the present invention may be a liquid oily component (an oily component that is liquid at room temperature (25°C)) that is commonly used in cosmetics and the like, and is not particularly limited. Examples include ester oil, liquid fats and oils, hydrocarbon oils, silicone oils, etc. These liquid oils may be blended alone or in combination of two or more kinds.
[0022] Examples of ester oils include cetyl ethylhexanoate, triethylhexanoin, cetyl octanoate, hexyl laurate, isopropyl myristate, octyl palmitate, isocetyl stearate, isopropyl isostearate, octyl isopalmitate, isodecyl oleate, glyceryl tri-2-ethylhexanoate, pentaerythritol tetra-2-ethylhexanoate, 2-ethylhexyl succinate, and diethyl sebacate.
[0023] Examples of liquid oils and fats include linseed oil, camellia oil, macadamia nut oil, corn oil, mink oil, olive oil, avocado oil, camellia oil, castor oil, safflower oil, jojoba oil, sunflower oil, almond oil, rapeseed oil, sesame oil, soybean oil, peanut oil, triglycerin, glycerin trioctanoate, and glycerin triisopalmitate.
[0024] Examples of the hydrocarbon oil include liquid paraffin, squalane, squalene, paraffin, isoparaffin, and ceresin. Examples of silicone oils include chain silicones such as dimethylpolysiloxane, methylphenylpolysiloxane, and methylhydrogenpolysiloxane, and cyclic silicones such as octamethylcyclotetrasiloxane, decamethylcyclopentasiloxane, and dodecamethylcyclohexasiloxane.
[0025] In addition to the above examples, the (c) liquid oil component of the present invention also includes oil-based ultraviolet absorbers that are liquid at room temperature, such as ethylhexyl methoxycinnamate, and oil-based drugs that are liquid at room temperature, such as tocopherol. The cosmetic of the present invention may contain water-holding oil agents such as dimer dilinoleate (phytosteryl / isostearyl / cetyl / stearyl / behenyl), dimer dilinoleate di(isostearyl / phytosteryl), (isostearic acid / behenic acid) (glyceryl / polyglyceryl-6) esters, and dipentaerythrityl hexa(hydroxystearic acid / stearic acid / rosin acid), but the amount of these is preferably less than 1% by mass, more preferably less than 0.5% by mass.
[0026] The blending amount of the liquid oil (c) in the cosmetic of the present invention is 11 to 15% by mass, and preferably 12 to 14% by mass. If the blending amount is less than 11% by mass, the powder cosmetic is not densely molded, and there is a tendency for the powder to stick too much, and the impact resistance is also insufficient. If the blending amount exceeds 15% by mass, caking is likely to occur, which is undesirable.
[0027] In addition to the essential components (a) to (c) described above, the cosmetic of the present invention may contain other cosmetic ingredients that are typically used in solid cosmetic powders, such as powders (other than the above (a) and (b)), solid or semi-solid oils, surfactants, moisturizers, thickeners, fragrances, antioxidants, and various drugs.
[0028] Specific examples of powders (other than (a) and (b) above) include organic pigments (e.g., Red No. 104, Red No. 202, Red No. 226, Yellow No. 4, Yellow No. 5, Blue No. 1, Black No. 401, etc.); lake pigments (e.g., Yellow No. 4 Aluminum Lake, Blue No. 1 Aluminum Lake, etc.); inorganic color pigments (e.g., yellow iron oxide, red iron oxide, black iron oxide, chromium oxide, chromium hydroxide, carbon black, ultramarine, Prussian blue, manganese violet, etc.); inorganic white pigments (e.g., zinc oxide, titanium oxide (pigment grade), etc.); extender pigments (e.g., talc, mica, sericite, etc.); other inorganic pigments (e.g., , barium sulfate, calcium carbonate, magnesium carbonate, aluminum silicate, magnesium silicate, silica, alumina, boron nitride, etc.); spherical resin powders (for example, polyethylene powder, polypropylene powder, polymethyl methacrylate powder, nylon powder, polytetrafluoroethylene powder, silicone powders (for example, (vinyl dimethicone / methicone silsesquioxane) crosspolymer, etc.), silicone rubber powder, silk powder, urethane powder, cellulose powder, polyfluoride, etc.); metal soap powders, etc. When the cosmetic of the present invention contains boron nitride, the amount of boron nitride blended is preferably less than 10% by mass, and more preferably less than 5% by mass.
[0029] The size, shape, etc. of these powders are not particularly limited, and they can be used alone or in combination of two or more. These powders may also be subjected to a suitable surface treatment. The surface hydrophobization treatment can be performed using the methods described above for the fine particle titanium oxide.
[0030] When using extender pigments such as talc or mica as the powder (other than (a) and (b)) blended in the cosmetic of the present invention, it is preferable that the surface of these extender pigments is coated with an elastomer consisting of (A) a silicone polymer having an amino group and (B) a silicone polymer having a carboxyl group or an acrylic polymer having a carboxyl group. In the elastomer, the molar ratio of amino groups to carboxyl groups is Y / X=0.1 to 1.2 (Y is the molar amount of carboxyl groups contained in component (B), and X is the molar number of amino groups contained in component (A)). Details of the elastomer are described in JP 2017-214565 A.
[0031] The elastomer has the following formula (1): [ka] a silicone polymer having an amino group represented by the formula: [wherein X is an alkyl group having 1 to 18 carbon atoms, R is an alkylene group (preferably a propylene group), R' is an alkylene group (preferably an ethylene group), m is a number from 20 to 2000, and n is a number from 1 to 100] (side-chain type amino-modified silicone: component (A)); The following formula (2): [ka] [In the formula, R1 and R2 are a methyl group or a group represented by the following formula (2'), the compound contains 1 to 100 groups represented by the following formula (2') in one molecule, and y represents a number from 1 to 50,000.] [ka] or a silicone polymer having a carboxyl group represented by the following formula (3): [ka] and an acrylic polymer having a carboxyl group represented by the formula: [wherein m / (m+n)=0 to 0.5].
[0032] The cosmetic of the present invention preferably contains 10% by mass to 50% by mass of the extender pigment (e.g., talc) surface-coated with the elastomer, based on the total amount of the cosmetic, thereby further improving the feel when used and impact resistance. On the other hand, the cosmetic of the present invention does not need to contain fluorine-treated talc.
[0033] The cosmetic of the present invention has sufficiently excellent impact resistance by combining the above essential components (a), (b) and (c), and therefore does not need to contain a powder binder such as sodium stearyl fumarate, which is sometimes used in conventional powder cosmetic preparations.
[0034] The cosmetic of the present invention can be manufactured according to a method conventionally used for manufacturing solid cosmetic powders. For example, either dry molding, in which the powder component and oily component are mixed without adding a solvent, filled into a container, and molded under pressure, or wet molding, in which a volatile dispersion medium is added to the powder component and oily component to form a slurry, filled into a container in the slurry state, and solidified by removing the solvent by vacuum suction or the like, may be used. However, from the viewpoint of excellent impact resistance, it is preferable to manufacture by wet molding, particularly wet molding using an aqueous solvent.
[0035] Therefore, the present invention provides a method for producing a powder solid cosmetic product, which comprises dissolving or dispersing a raw material mixture containing (a) 20 to 30% by mass of glass flakes, based on the total amount of the raw material mixture, (b) 4 to 10% by mass of fine titanium dioxide particles, based on the total amount of the raw material mixture, and (c) 11 to 15% by mass of a liquid oil, based on the total amount of the raw material mixture, in a volatile dispersion medium, filling the raw material mixture into a container, and then removing the volatile dispersion medium.
[0036] In the production method of the present invention, the volatile dispersion medium contains water as a primary dispersion medium and a water-soluble organic solvent (e.g., ethanol, acetone, isopropyl alcohol, etc.) as a secondary dispersion medium in an amount of 0 to 30 mass %, preferably 1 to 30 mass %, and the contact angle of the volatile dispersion medium with the mixture dissolved or dispersed in the volatile dispersion medium is 125 degrees or more, preferably 125 degrees to 135 degrees.
[0037] In the above-mentioned production method, it is preferable that the mixture does not substantially contain a surfactant and does not substantially contain a polyhydric alcohol. Also, as described above, in the present invention, it is not necessary to attach fine titanium dioxide particles to the surface of the glass flakes.
[0038] The powder solid cosmetic preparation of the present invention contains a larger amount of glass flakes than conventional products, and has excellent transparency and luster. In addition, glass flakes impart a moderate pearly feel compared to other commonly used pearlescent agents, so it is particularly suitable for use as a makeup top coat, makeup base, foundation, or face powder. EXAMPLES
[0039] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. The blend amounts are expressed in mass % unless otherwise specified.
[0040] Each example of a solid cosmetic powder was produced according to the formulation shown in Tables 1 and 2 below. A panel of experts applied each example of the cosmetic material to the skin, and visually evaluated the transparency of the cosmetic coating film. A: Excellent transparency B: Not enough transparency C: Not measured
[0041] Impact resistance was confirmed by a drop test from a height of 30 cm, and was evaluated based on the number of drops required before the product broke. A: 7 or more times B: 5~6 times C: 4 times or less
[0042] As shown in Tables 1 and 2, the cosmetic compositions of the present invention (Examples 1 to 3) containing 20 to 30% by mass of glass flakes, 4 to 10% by mass of fine titanium oxide, and 11 to 15% by mass of liquid oil were excellent in transparency and had high impact resistance. In contrast, Comparative Example 1, in which the amount of fine titanium oxide was less than 4% by mass, and Comparative Example 2, which did not contain fine titanium oxide, showed reduced impact resistance. In Comparative Example 3, in which pigment-grade titanium oxide (average particle size = 250 nm) was used instead of fine titanium oxide, the impact resistance did not improve and the transparency decreased. The impact resistance decreased even when the amount of liquid oil was 10% by mass (Comparative Example 4), and became completely brittle when the amount was less than 10% by mass (Comparative Example 5). On the other hand, when the amount of glass flakes was less than 20% by mass, the composition lacked transparency (Comparative Example 6).
[0043] [Table 1]
[0044] [Table 2]
[0045] Other formulation examples of the solid cosmetic preparation in powder form according to the present invention are given below. The following formulation examples were evaluated in the same manner as in the above examples, and all of the formulations were rated as "A" in terms of "transparency" and "impact resistance (drop test)."
[0046] Prescription Example 1 Ingredients Amount (mass%) Elastomer coated talc 9.77 Mica 5 Boron Nitride 4 Glass flakes (※11) 30 Fine particle titanium dioxide (※12) 3.5 Fine particle titanium dioxide (※13) 3.5 Pigment-grade titanium dioxide (※14) 10 Zinc Oxide 3 Red iron oxide 0.36 Yellow iron oxide 2.2 Black iron oxide 0.17 (Vinyl Dimethicone / Methicone Silsesquioxane) Crosspolymer (※15) 15 Dimethicone 2.5 Diphenylsiloxyphenyl Trimethicone 1 Cetyl ethylhexanoate 5 Ethylhexyl methoxycinnamate 5 Total 100 *11: Silky Flake (registered trademark) FTD010FY-F01 (average particle size 10 μm) *12: MT-100TV (product name: Teika Corporation) (average particle size 15 nm) *13: Stearic acid-treated titanium dioxide fine particles (average particle size 30-35 nm) *14:RC402P (product name) *15: KSP-100 (product name: Shin-Etsu Chemical Co., Ltd.)
[0047] Prescription Example 2 Ingredients Amount (mass%) Elastomer coated talc 22.41 Mica 5 Boron Nitride 4 Glass flakes (※21) 30 Fine particle titanium dioxide (※22) 3.5 Fine particle titanium dioxide (※23) 3.5 Zinc Oxide 3 Red iron oxide 0.03 Yellow iron oxide 0.06 Spherical powder (**) 15 Dimethicone 2.5 Diphenylsiloxyphenyl Trimethicone 1 Cetyl ethylhexanoate 5 Ethylhexyl methoxycinnamate 5 Total 100 *21: Silky Flake (registered trademark) FTD010FY-F01 (average particle size 10 μm) *22: MT-100TV (product name: Teika Corporation) (average particle size 15 nm) *23: Stearic acid-treated titanium dioxide fine particles (average particle size 30-35 nm) **: Nylon spherical powder (Nylon SP-500: Nikko Rikagaku Sangyo Co., Ltd.), porous spherical silica (Sunsphere L-51: AGC Si-Tech Co., Ltd.), or non-porous spherical silica (Sunsphere NP-30: AGC Si-Tech Co., Ltd.)
[0048] Prescription Example 3 Ingredients Amount (mass%) Elastomer coated talc 22.41 Mica 5 Boron Nitride 4 Glass flakes (※31) 30 Fine particle titanium dioxide (※32) 3.5 Fine particle titanium dioxide (※33) 3.5 Zinc Oxide 3 Red iron oxide 0.03 Yellow iron oxide 0.06 (Vinyl Dimethicone / Methicone Silsesquioxane) Crosspolymer (※34) 15 Dimethicone 2.5 Diphenylsiloxyphenyl Trimethicone 1 Cetyl ethylhexanoate 5 Ethylhexyl methoxycinnamate 5 Total 100 *31: Silky Flake (registered trademark) FTD025FY-F02 (particle size: 25 μm) *32: MT-100TV (product name: Teika Corporation) (average particle size 15 nm) *33: Stearic acid-treated titanium dioxide fine particles (average particle size 30-35 nm) *34: KSP-100 (product name: Shin-Etsu Chemical Co., Ltd.)
Claims
1. (a) 20 to 30% by weight of glass flakes; (b) 5 to 10 mass % of fine particle titanium dioxide; and (c) A solid cosmetic preparation in powder form, characterized in that it contains 11 to 15% by mass of liquid oil.
2. 2. The cosmetic according to claim 1, wherein the glass flakes (a) have an average thickness of 0.1 to 1 μm, an average particle size (D50) of 1 to 50 μm, and an aspect ratio of 10 or more.
3. 3. The cosmetic preparation according to claim 1, wherein the average primary particle size of the fine titanium dioxide particles (b) is 10 nm to 100 nm.
4. 4. The cosmetic preparation according to claim 1, further comprising an extender pigment whose surface is coated with an elastomer consisting of (A) a silicone polymer having an amino group, and (B) a silicone polymer having a carboxyl group or an acrylic polymer having a carboxyl group, wherein the molar ratio of amino groups to carboxyl groups is Y / X=0.1 to 1.2 (Y is the molar amount of carboxyl groups contained in component (B), and X is the molar amount of amino groups contained in component (A)).
5. The cosmetic preparation according to claim 1 , which is a makeup top coat, a makeup base coat, a foundation, or a powder.
6. 6. A method for producing a solid cosmetic product in powder form according to any one of claims 1 to 5, comprising dissolving or dispersing a raw material mixture containing (a) 20 to 30% by mass of glass flakes based on the total amount of the raw material mixture, (b) 5 to 10% by mass of fine titanium dioxide based on the total amount of the raw material mixture, and (c) 11 to 15% by mass of liquid oil based on the total amount of the raw material mixture in a volatile dispersion medium, filling the raw material mixture into a container, and then removing the volatile dispersion medium, The volatile dispersion medium contains water as a main dispersion medium and a water-soluble organic solvent as a sub-dispersion medium in an amount of 0 to 30 mass %, and the volatile dispersion medium has a contact angle of 125 degrees or more with respect to the mixture to be dissolved or dispersed in the volatile dispersion medium.
Citation Information
Patent Citations
Eye shadow
JP1995215822A
Flaky powder and cosmetic compounded therewith
JP1997071417A
Powdery solid cosmetic
JP2000186012A
Powdery solid cosmetic
JP2010077043A
Solid powder cosmetic production method
JP2016037496A